Simplifying
-2 + 8 = -5x + 7 + 4
Combine like terms: -2 + 8 = 6
6 = -5x + 7 + 4
Reorder the terms:
6 = 7 + 4 + -5x
Combine like terms: 7 + 4 = 11
6 = 11 + -5x
Solving
6 = 11 + -5x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '5x' to each side of the equation.
6 + 5x = 11 + -5x + 5x
Combine like terms: -5x + 5x = 0
6 + 5x = 11 + 0
6 + 5x = 11
Add '-6' to each side of the equation.
6 + -6 + 5x = 11 + -6
Combine like terms: 6 + -6 = 0
0 + 5x = 11 + -6
5x = 11 + -6
Combine like terms: 11 + -6 = 5
5x = 5
Divide each side by '5'.
x = 1
Simplifying
x = 1